1991
DOI: 10.1164/ajrccm/144.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Severe Community-acquired Pneumonia: Epidemiology and Prognostic Factors

Abstract: Over a period of 4 consecutive yr, 92 nonimmunosuppressed patients (21 women and 71 men aged 53 +/- 16 yr, means = SD) with critical acute respiratory failure (PaO2/FiO2, 209 +/- 9 mm Hg) caused by severe community-acquired pneumonia were admitted to the respiratory intensive care unit (RICU) of a general hospital. The most frequent underlying clinical condition was chronic obstructive pulmonary disease (44 patients, 48%). A total of 56 patients (61%) required mechanical ventilation for a mean period of 10.7 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
295
5
40

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 548 publications
(360 citation statements)
references
References 16 publications
13
295
5
40
Order By: Relevance
“…The reported incidence of LD in CAP ranges from 1.6% to 7.5% [2][3][4][5][6] and that in severe CAP is between 14% and 22.8%) [6][7][8]. Legionnaires' disease has appeared in hospitals, long-term care facilities and other types of accommodation [9][10][11][12][13][14][15], causing serious problems.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of LD in CAP ranges from 1.6% to 7.5% [2][3][4][5][6] and that in severe CAP is between 14% and 22.8%) [6][7][8]. Legionnaires' disease has appeared in hospitals, long-term care facilities and other types of accommodation [9][10][11][12][13][14][15], causing serious problems.…”
Section: Introductionmentioning
confidence: 99%
“…36.36% of the patients were either hypertensive or diabetic and 9% were both hypertensive and diabetic. Many articles have shown a link between chronic obstructive pulmonary disease and community-acquired pneumonia in that episodes of AECOPD could be associated with an episode of CAP [13][14][15][16][17][18] , and also CAP as a complication of the long term use of potent inhalational steroids used for the control of COPD. 22,23 COPD is considered as a risk factor for CAP, and previous studies of CAP including inpatient, outpatient, and ICU cohorts have shown that COPD is frequently reported as a co-morbid condition.…”
Section: Discussionmentioning
confidence: 99%
“…Woodhead et al [65] have shown that administration of antibiotics by general practitioners before admission reduces subsequent inhospital mortality. Similarly, delay or inadequate antibiotic therapy after admission to hospital [66] or before admission to the intensive care unit (ICU) [67] is associated with increased mortality in patients admitted to hospital and ICU respectively.…”
Section: Discussionmentioning
confidence: 99%